Aplikasi Edible Coating Lidah Buaya pada Jamur Tiram dan Pengaruhnya terhadap Mutu Kimia, Fisik, dan Sensoris Selama Penyimpanan - Alief Ababiel; Siti Aminah; Agus Suyanto (Universitas Muhammadiyah Semarang, 2023)
Oyster mushroom is the most potential raw materials to be developed in Indonesia because it contains protein and high nutritional value. However, oyster mushrooms are easily wilted and rotten because they are still undergoing post-harvest metabolic and respiratory processes. Edible coating is a thin layer of edible material that has ability to replace the natural wax layer that is lost in post-harvest handling. The purpose of this research was to determine the effect of aloe vera edible coating application on oyster mushrooms to chemical, physical, and sensory characteristics during storage. The research method is an experimental type using a Completely Randomized Design (RAL) consisting of 1 factor 5 treatments, namely aloe vera gel concentrations of 0, 25, 50, 75, and 100%. The steps involved are making edible coatings and then coating oyster mushrooms with edible coating. The analysis of this research included analysis of protein content (Kjedahl method), moisture content (drying method), weight loss, texture, color, and sensory characteristics (hedonic quality). The results showed that there was an effect of edible coating application on the chemical, physical, and sensory qualities of oyster mushrooms during storage. Tests were carried out on the 1st and 4th days. The best treatment was obtained from 100% aloe vera gel concentration which produced an average protein content (2.965%), water content (17.221%), weight loss (21.553%), texture (0.845 mm), color degree (63.578), and quality. hedonic (4,3).